The Salvadoran migration - Colindres, Eduardo B. (Entorno, 2002)
Many Salvadorans from time immemorial for diverse reasons or circumstances, natural as earthquakes or produced by the human being, as wars and political persecutions; they have had to emigrate from the homeland to conserve their life and produce the necessary goods for their subsistence, since El Salvador did not provide them with the minimum requirements demanded by their development and development as a human being in construction and improvement. This migration in most cases was not the result of the emigrant's free desire to leave El Salvador, but was forced through legal action or social production conditions that encouraged emigration. Legally it was done through the different institutions that forced the Indians in time to provide their services in the encomienda’s and properties of Spaniards and Creoles.